2015
DOI: 10.1186/s13014-015-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Excellent local control and survival after postoperative or definitive radiation therapy for sarcomas of the head and neck

Abstract: BackgroundTo report our results with postoperative or definitive radiation therapy in head and neck sarcomas.MethodsWe performed a retrospective analysis of 26 patients suffering from head and neck sarcomas, who received postoperative or definitive radiation therapy between 2003 and 2012. Median age was 64 years (19–88) and 69 % were male. Tumor locations were skull (including skin) in 31 %, paranasal sinus/orbita in 27 % and neck (including pharynx/larynx) in 42 %. Median tumor size was 4.6 cm (1-12 cm). 22 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
(53 reference statements)
2
16
0
4
Order By: Relevance
“…In sarcomas, the improvement in locoregional control and overall survival achieved by the addition of radiation has shown to be related to tumor grade and the narrowness of the surgical margins [27]. As extensive surgical margins are often difficult to accomplish in the neck region, it has been shown that postoperative radiation may improve local control rates [28]. Chemotherapy was included in 23.08% of the cases, as recommended for patients previously treated by surgery and/or radiation with metastatic or recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…In sarcomas, the improvement in locoregional control and overall survival achieved by the addition of radiation has shown to be related to tumor grade and the narrowness of the surgical margins [27]. As extensive surgical margins are often difficult to accomplish in the neck region, it has been shown that postoperative radiation may improve local control rates [28]. Chemotherapy was included in 23.08% of the cases, as recommended for patients previously treated by surgery and/or radiation with metastatic or recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, radiotherapy can occasionally provide a durable remission although local recurrence rates are high. Outcomes appear related to tumour size, grade, and radiation dose [5659]; doses of over 60 Gy may be employed. In patients with significant life-limiting comorbidities lower dose, palliative radiotherapy is an option.…”
Section: Management Of Localised Diseasementioning
confidence: 99%
“…Radiation treatment confers an improvement in local control, but not overall survival . However, excellent survival rates have been reported after definitive or postoperative radiation treatment for sarcoma of the head and neck region …”
Section: Discussionmentioning
confidence: 99%